Revalidation of the First Step Act Risk Assessment: A Test of Predictive Strength, Dynamic Validity, and Racial/Ethnic Neutrality - Labrecque, Ryan (Crime & delinquency, 2025)
The First Step Act mandated the development and implementation a risk and needs assessment system for the Federal Bureau of Prisons (BOP). In response, the Prisoner Assessment Tool Targeting Estimated Risk and Needs (PATTERN) was created to assess the risk of recidivism among each person in BOP custody. This investigation represents the first external validation of PATTERN. Results indicated PATTERN is highly predictive of both general and violent recidivism, individuals are capable of changing risk scores and levels while in custody, and changes in risk levels are associated with meaningful differences in recidivism risk. Although PATTERN was accurate in predicting recidivism across all five racial/ethnic groups examined, it also overpredicted recidivism among some groups and underpredicted recidivism for others.